Event-related delta and theta synchronization during explicit and implicit emotion processing - Knyazev, G.G.; Slobodskoj-Plusnin, J.Y.; Bocharov, A.V. (Neuroscience, 2009)
Emotion information processing may occur in two modes which are differently represented in conscious awareness. Fast online processing involves coarse-grained analysis of salient features, and is not represented in conscious awareness; offline processing takes hundreds of milliseconds to generate fine-grained analysis, and is represented in conscious awareness. These processing modes may be studied using event-related electroencephalogram theta and delta synchronization as a marker of emotion processing. Two experiments were conducted, which differed on the mode of emotional information presentation. In the explicit mode subjects were explicitly instructed to evaluate the emotional content of presented stimuli; in the implicit mode they performed a gender discrimination task. Firstly, we show that in both experiments theta and delta synchronization is stronger upon presentation of “emotional” than “neutral” stimuli, and in subjects who are more sensitive, or experience higher emotional involvement than in less sensitive or detached subjects. Secondly, we show that in the implicit mode theta and delta synchronization is more pronounced in an early (before 250 ms post-stimulus) processing stage, whereas in the explicit mode it is more pronounced in a later processing stage. Source localization analysis showed that implicit processing of angry and happy (relative to neutral) faces is associated with higher early (before 250 ms) theta synchronization in the right parietal cortex and the right insula, respectively. Explicit processing of angry and happy faces is associated with higher late (after 250 ms) theta synchronization in the left temporal lobe and bilateral prefrontal cortex, respectively.